VD_FINDINFO Arrêt / 2011 / 472 vom 7. März 2011 - VD Tribunal cantonal (2011)
RENTE D'INVALIDITÉ, LOI FÉDÉRALE SUR L'ASSURANCE-ACCIDENTS, DEGRÉ DE L'INVALIDITÉ | 18 LAA, 6 al. 1 LAA, 16 LPGA, 7 LPGA, 8 al. 1 LPGA